Beyond Fate and Hopelessness : The Need for a Contextual Approach to HIV/AIDS Prevention Programmes in the Evangelical Christian Community of French-Speaking Africa - Van den Toren-Lekkerkerker, Berdine (Transformation: An International Journal of Holistic Mission Studies, 2014)
Awareness, care and preventative action regarding HIV/AIDS, and those affected by it, is growing in the evangelical Christian Community in French-speaking Sub-Saharan Africa. Yet, even though the issues seem to be addressed through teaching and preaching in the churches, the real issues, questions and struggles of the people are not discussed. This article describes some of the most important outcomes of a qualitative research in this people group, looking at the values and beliefs around sexuality and community and what impact they have on current HIV/AIDS prevention practices and strategies. This description highlights the seeming discrepancy between people’s values and their daily lives, the role community can play – as both a community of grace and a countercultural yet contextually relevant community, and the role of leaders, grass-root communities and partnership processes in strategy development. This article argues for a contextual relevant approach in which the specific evangelical worldview is encountered as a possible strength, rather than a problem.
Free
Keywords: Africa; African Christianity; Christian ethics; Christianity; Churches; Collaboration; Communities; Community relations; Cultural identity; Evangelical Churches; HIV/Aids prevention strategy; Primate lentiviruses; Theology; community; contextualization; theology